2000
DOI: 10.1001/jama.284.12.1541
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of a New Vibrio parahaemolyticus Serotype in Raw Oysters

Abstract: This is the first reported outbreak of V parahaemolyticus serotype O3:K6 infection in the United States. The emergence of a virulent serotype and elevated seawater temperatures and salinity levels may have contributed to this large multistate outbreak of V parahaemolyticus. Bacteriologic monitoring at harvest sites did not prevent this outbreak, suggesting that current policy and regulations regarding the safety of raw oysters require reevaluation. Consumers and physicians should understand that raw or underco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
84
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 19 publications
(14 reference statements)
2
84
0
8
Order By: Relevance
“…Vibrio parahaemolyticus is of significant medical importance, as it is the leading cause of seafood-associated bacterial gastroenteritis worldwide (20)(21)(22)(23). Generally, the bacterium infects the host through the gastrointestinal tract, where it encounters stress conditions such as low pH, bile salts, antimicrobial peptides, and low salinity as well as challenges from the host immune system.…”
mentioning
confidence: 99%
“…Vibrio parahaemolyticus is of significant medical importance, as it is the leading cause of seafood-associated bacterial gastroenteritis worldwide (20)(21)(22)(23). Generally, the bacterium infects the host through the gastrointestinal tract, where it encounters stress conditions such as low pH, bile salts, antimicrobial peptides, and low salinity as well as challenges from the host immune system.…”
mentioning
confidence: 99%
“…parahaemolyticus ( 3 , 4 ). Stool samples of 60 patients with acute diarrhea were analyzed by standard procedures ( 5 , 6 ). Serotyping confirmed that all V .…”
mentioning
confidence: 99%
“…Serotyping confirmed that all V . parahaemolyticus isolates were O3:K6 ( 5 , 6 ), did not produce urease, and showed the Kanagawa phenomenon (virulence-associated hemolysis) ( 5 8 ). PCR analysis indicated that the genome of these isolates contained tdh , tlh , and toxRS /new open reading frame 8 DNA sequences and lacked trh sequences ( 1 , 7 ), which are consistent with molecular characteristics of the pandemic clone O3:K6 ( 1 , 5 8 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations